Dose and Efficacy of Bevacizumab in Recurrent High-Grade Gliomas: A Retrospective Study - Bai X; Xing H; Feng M; Ma W; Wang S (Cancer Management and Research)
Xuexue Bai,1 Hao Xing,1 Ming Feng,1 Wenbin Ma,1 Shiyong Wang2 1Department of Neurosurgery, Peking Union Medical College Hospital, Chinese Academy of Medical Science and Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Neurosurgery, The First Affiliated Hospital of Jinan University, Guangzhou, Guangdong, People’s Republic of ChinaCorrespondence: Ming Feng; Shiyong Wang, Email pumchfming@126.com; Washiyong@126.comPurpose: We retrospectively analyzed the effect of Bevacizumab (BEV) on recurrent high-grade glioma (rHGG) and examined the relationship between dose and efficacy.Methods: A total of 182 patients with rHGG were included in this study. Patients were divided into a non-BEV group and a BEV group according to the treatment they received, and the BEV group was further divided into a low-dose group and a high-dose group based on the dose. Depending on the number of groups and the characteristics of numerical variables, t-test, ANOVA, or rank-sum test were selected. Categorical variables were compared using the chi-squared test.Results: Progression-free survival (PFS) was lower in the non-BEV group compared to the BEV group, while overall survival (OS) was not different between the two groups. There was no difference in PFS and OS between low-dose group and high-dose group. Notably, we found that patients with longer PFS and OS were more likely to be from the BEV group. In addition, differences in Karnofsky Performance Score (KPS), steroid dose, and brain edema were observed in the non-BEV, low-dose, and high-dose groups from 3 to 12 months after treatment.Conclusion: BEV can improve PFS in patients with rHGG, although its impact on OS is limited. There was no difference in the efficacy of different doses of BEV on rHGG. Interestingly, patients with longer PFS and OS were more likely to be from the BEV group. Based on these findings, long-term low-dose BEV appears to be an effective treatment option for rHGG.Keywords: bevacizumab, temozolomide, recurrent high-grade glioma, progression free survival, overall survival